Zymography of Hybrid Layers Created Using Extrafibrillar Demineralization - Gu, L.; Mazzoni, A.; Gou, Y.; Pucci, C. [UNESP]; Breschi, L.; Pashley, D. H.; Niu, L.; Tay, F. R. (SAGE Publications, 2018)
A chelate-and-rinse extrafibrillar calcium chelation dentin bonding concept has recently been developed and investigated for its effectiveness in improving resin-dentin bonding by bridging the gap between wet and dry dentin bonding. The objective of the present study was to evaluate the gelatinolytic activity of hybrid layers (HLs) created using the chelate-and-rinse bonding technique. Gelatinolytic activity within the HL was examined using in situ zymography and confocal laser-scanning microscopy after 24-h storage or after thermomechanical cycling. Dentin specimens were bonded with Prime&Bond NT (Dentsply Sirona) after conditioning with 15 wt% phosphoric acid for 15 s (control) or 15 wt% polymeric chelators (sodium salt of polyacrylic acid; PAAN) of 2 different molecular weights for 60 s. For each reagent, bonding was performed using dry-bonding and wet-bonding techniques (n = 10). Slices containing the adhesive-dentin interface were covered with fluorescein-conjugated gelatin and examined with a confocal laser-scanning microscope. Fluorescence intensity emitted by the hydrolyzed fluorescein-conjugated gelatin was quantified. Gelatinolytic activity was expressed as the percentage of green fluorescence emitted within the HL. After storage for 24 h, enzymatic activity was only detected within the completely demineralized phosphoric acid–etched dentin, with values derived from dry bonding higher than those from wet bonding (P < 0.05). Almost no fluorescence signals were detected within the HL when dentin was conditioned with PAANs compared with the controls (P < 0.05). After thermomechanical cycling, enzymatic activities significantly increased for the phosphoric acid–conditioned, drying-bonding group compared with 24-h storage (P < 0.05). The present study showed that the use of the chelate-and-rinse bonding concept for both dry-bonding and wet-bonding approaches results in the near absence of matrix-bound collagenolytic activities in the HL even after aging. This may be attributed to fossilization of endogenous proteases via preservation of intrafibrillar minerals within the dentin collagen matrix.
Keywords: bonding; chelation; dentin; enzymology; matrix metalloproteinases; microscopy